ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Fitriani Rowiyatun (Universitas Muhammadiyah Yogyakarta, 2007)
the result indicate fincancial condition revised altman model and previous audit are significantly affect the going concern audit opinion